2019
DOI: 10.1088/1757-899x/550/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of shear bond strength of light-cured resin-modified glass ionomer and moist insensitive primer on contaminated enamel

Abstract: Despite rapid developments in adhesive technology, contamination of bonding surfaces remains a major problem. The aim of this study was to evaluate the influence of contamination on shear bond strength of two adhesive systems: resin-modified glass ionomer cement (Fuji Ortho LC; GC America Corp) and Moist Insensitive Primer (Transbond MIP, 3M Unitek) combination with Transbond XT (light-activated), under different enamel conditions. Metal brackets were bonded to the buccal surfaces of 42 human premolars. The to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…After biting for 5 minutes, cementation of the restoration is complete. Te process of light curing could shorten the occlusion time for patients and allow easy removal of the excess RMGIC, but there are few reports describing whether it can improve the bond strength [9][10][11]. Our previous studies have shown that the curing mode of dual-cured RMGIC can directly afect the fexural strength because the fexural strength in the lightcuring mode is higher than that in the chemical-curing mode and also could improve the mechanical chimerism of RMGIC [12].…”
Section: Introductionmentioning
confidence: 99%
“…After biting for 5 minutes, cementation of the restoration is complete. Te process of light curing could shorten the occlusion time for patients and allow easy removal of the excess RMGIC, but there are few reports describing whether it can improve the bond strength [9][10][11]. Our previous studies have shown that the curing mode of dual-cured RMGIC can directly afect the fexural strength because the fexural strength in the lightcuring mode is higher than that in the chemical-curing mode and also could improve the mechanical chimerism of RMGIC [12].…”
Section: Introductionmentioning
confidence: 99%